2021
DOI: 10.1111/raq.12566
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive update on inventory of finfish cell lines developed during the last decade (2010–2020)

Abstract: Cell culture has become an indispensable part of modern research and is considered the best alternatives for different biological research on whole animals as they mimic the host cellular genetic homogeneity and also reduces the variability of in vivo responses. Hence, there has been increasing development of cell lines by different research groups and companies globally. For this reason, to cover the dearth of knowledge of newly developed fish cell lines, we have made a comprehensive update on new fish cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 243 publications
(248 reference statements)
1
19
0
Order By: Relevance
“…Cryopreservation at different passage levels followed by the revival after two months of cryo-storage, the DRS cells were successfully recovered with a viability of 70-75% approximately, forming a con uent monolayer of cells after 7 days of plating, which indicates that the cryo-storage is not detrimental to the cells. No changes in the indicators of the functionality of cells, including morphology, attachment, and growth [30], were observed after recovery, which is in agreement with the earlier reports [32,45].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Cryopreservation at different passage levels followed by the revival after two months of cryo-storage, the DRS cells were successfully recovered with a viability of 70-75% approximately, forming a con uent monolayer of cells after 7 days of plating, which indicates that the cryo-storage is not detrimental to the cells. No changes in the indicators of the functionality of cells, including morphology, attachment, and growth [30], were observed after recovery, which is in agreement with the earlier reports [32,45].…”
Section: Discussionsupporting
confidence: 93%
“…Further, zebra sh skin also possesses a higher regeneration capacity similar to other organs such as ns, heart, and optic nerve [53]. Therefore, cell lines established from the skin tissue could be applicable in regenerative medicine for producing sh skin grafts [45] and the cytotoxicity assessment of silica nanoparticles [9]. Zebra sh skin also offers a relevant biological model to study pigment research [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fish cell lines are an extremely valuable tool because of their low cost and reproducibility and are widely used in cell biology, oncology, genomics, genetics, and resource conservation [ 1 , 40 ]. The present study reported the establishment of the C.nasus gonadal somatic cell line and differentiation of medaka SG3 into sperm, which verifies the effect of somatic cells on spermatogonial stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts or other extracellular matrix-secreting cell types could also be incorporated. Fortunately, fibroblast-like cells and cells derived from fin tissue are abundant among fish cell lines (Thangaraj et al 2021 ) and are easily isolated and cultured. Future research into the use of fibroblasts in CS should focus on identifying optimal culture conditions for serum-free co-cultures of fibroblasts with myogenic and adipogenic cells and investigating the effects of these cell types on one another’s proliferation and differentiation.…”
Section: Fish Connective Tissue Vascular Tissue and Skinmentioning
confidence: 99%